Adherencia al tratamiento en niñas y niños con VIH - Ruiz Navia , Ana María (2022)
The article discusses and determines the degree of adherence to HIV/AIDS treatment in children while considering the behaviors and the variables associated with the disease. The study was adjusted for 1 male and 5 female children diagnosed with HIV and their primary caregivers. A semi-structured interview evaluating treatment adherence for children with HIV/AIDS ad hoc was conducted with the 6 children. The primary caregivers underwent a modified version of the semi-structured interview evaluating children’s HIV/AIDS treatment adherence ad hoc. The results show the presence of adherence conducts in the study’s participants, evidenced by a series of variables determined for these behavioral conducts. Five of the participants were 95% adherent to treatment, while one participant was determined to be under this percentage level. The study revealed two main findings which influenced children’s adherence to HIV/AIDS treatment; the children’s emotional state and the importance of their primary caregivers’ role.